2017
DOI: 10.1177/016146811711900806
|View full text |Cite
|
Sign up to set email alerts
|

The Arts, the Common Core, and English Language Development in the Primary Grades

Abstract: Background/Context Throughout schooling, English learners (ELs) perform well below their monolingual English-speaking peers on literacy assessments, and Hispanics make up the majority of EL students in the United States. There is a strong consensus about the importance of early English oral language skills for ELs’ literacy development, yet teachers are not adequately prepared to meet the needs of these young learners. Historically, policy has not provided incentives for educators to focus on oral language dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Although many studies have shown associations between participation in the arts in general and enhanced child cognitive, social, and academic outcomes (Brown et al, 2017;Brown & Sax, 2013;Catterall, 2009;Catterall et al, 2012;Elpus, 2013a) and some have explored positive benefits for dance engagement in particular (Gilbert, 2006;Greenfader & Brouillette, 2017;Kim, 2007;Lobo & Winsler, 2006;Minton, 2003;Morgan & Stengel-Mohr, 2014;Park, 2007;Rossberg-Gempton et al, 1999;Seham, 1997), much of the research is correlational and does not adequately control for preexisting selection effects-the many ways that students who do and do not get arts experiences are initially different. Further, studies often examine rather global arts experiences (Catterall, 2009;Catterall et al, 2012;Winsler et al, 2019) when outcomes associated with arts participation are likely to vary by the particular art form in question (Winner et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although many studies have shown associations between participation in the arts in general and enhanced child cognitive, social, and academic outcomes (Brown et al, 2017;Brown & Sax, 2013;Catterall, 2009;Catterall et al, 2012;Elpus, 2013a) and some have explored positive benefits for dance engagement in particular (Gilbert, 2006;Greenfader & Brouillette, 2017;Kim, 2007;Lobo & Winsler, 2006;Minton, 2003;Morgan & Stengel-Mohr, 2014;Park, 2007;Rossberg-Gempton et al, 1999;Seham, 1997), much of the research is correlational and does not adequately control for preexisting selection effects-the many ways that students who do and do not get arts experiences are initially different. Further, studies often examine rather global arts experiences (Catterall, 2009;Catterall et al, 2012;Winsler et al, 2019) when outcomes associated with arts participation are likely to vary by the particular art form in question (Winner et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…First and most important, the research linking arts involvement and increased academic or developmental outcomes is largely correlational or quasi-experimental (somewhat better but still lacking sufficient control of selection variables), which only shows (often weak) associations between arts participation and positive developmental outcomes. There exist a few true experimental studies that have randomly assigned students to arts participation and control groups (the design needed to infer causality) that have shown positive effects of arts engagement (Greenfader & Brouillette, 2017; Holochwost et al, 2017; Lobo & Winsler, 2006; Moreno et al, 2011; Rabinowitch & Meltzoff, 2017; Schellenberg, 2004). However, the majority of research in this area compare an arts-exposed group with a naturally occurring comparison group of children not exposed to the art form in question without sufficiently accounting for selection factors.…”
Section: Methodological Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…Children who participated in an in-school drama and dance intervention integrating movement, gesture, and expression into early English literacy lessons showed greater gains in language acquisition and science vocabulary compared to a control group (Greenfader, Brouillette, & Farkas, 2015). In a recent study involving random assignment of teachers to professional development using drama techniques for teaching language arts, enhanced English acquisition among English Language Learners (ELLs) was found compared to regular professional development (Greenfader & Brouillette, 2017). Goldstein and Lerner (2017) assigned low-income 4-year-olds to a program involving repeated dramatic pretend play games and found enhanced emotional self-control for participants compared to controls.…”
Section: The Arts and Academic Achievementmentioning
confidence: 99%